2019
DOI: 10.1371/journal.pone.0213590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic infused calcium sulfate/hydroxyapatite (CAS/HA) insets on implant-associated osteitis in a femur fracture model in mice

Abstract: Cerament (Bonesupport Holding, Lund, Sweden) is a bioresorbable synthetic bone substitute consisting of calcium sulfate and hydroxyapatite which is successfully used as a bone graft in bone defects or in delayed and non-unions after fractures. Besides, calcium sulfate/ hydroxyapatite (CAS/HA) could have, attributed to its composition and osteoinductive properties, have great importance in the treatment of bone infections with critical size defects (CSD). Aim of the study was to evaluate the effects of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Therefore, it was concluded that the application of the antimicrobial-impregnated material in an acute implant-associated infection did not cure the lesion. 10 This corresponds to the findings of the present preclinical study. In accordance with our observations, biofilm formation in antimicrobial-loaded carriers has also been described in the clinic.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, it was concluded that the application of the antimicrobial-impregnated material in an acute implant-associated infection did not cure the lesion. 10 This corresponds to the findings of the present preclinical study. In accordance with our observations, biofilm formation in antimicrobial-loaded carriers has also been described in the clinic.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent preclinical study, the effect of CERAMENT|G was evaluated in a murine fracture model of implant-related S. aureus osteitis. 10 Lavage and debridement was performed before implantation of the product, and a final lavage was obtained again on the day of euthanization. 10 Although based on lavage, and not bone tissue samples, all samples were positive for bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of infections and osteomyelitis after complex fractures is high, ranging from 1 to 55% in primary fracture stabilization, especially in open fractures with extensive tissue damage [4][5][6][7][8]. Staphylococcus aureus is the most common pathogen associated with infected metal implants [9][10][11].…”
Section: Introductionmentioning
confidence: 99%